The helper component-proteinase of the Zucchini yellow mosaic virus inhibits the Hua Enhancer 1 methyltransferase activity in vitro - Jamous, Rana M.; Boonrod, Kajohn; Fuellgrabe, Marc W.; Ali-Shtayeh, Mohammed S.; Krczal, Gabi; Wassenegger, Michael (Journal of general virology, 2011)
The helper component-proteinase (HC-Pro) is a multifunctional protein found among potyviruses. With respect to its silencing suppressor function, small RNA binding appears to be the major activity of HC-Pro. HC-Pro could also exhibit other suppressor activities. HC-Pro may inhibit the Hua Enhancer 1 (HEN1) activity. There is indirect evidence showing that either transient or stable expression of HC-Pro in plants results in an increase of non-methylated small RNAs. Here, we demonstrated that recombinant Zucchini yellow mosaic virus (ZYMV) HC-Pro inhibited the methyltransferase activity of HEN1 in vitro. Moreover, we found that the HC-ProFINK mutant, which has lost small RNA-binding activity, inhibited HEN1 activity, while the truncated proteins and total soluble bacterial proteins did not. Using the ELISA-binding assay, we provided evidence that the HC-ProFRNK wild-type and HC-ProFINK both bound to HEN1, with HC-ProFRNK binding stronger than HC-ProFINK. Motif mapping analysis revealed that the amino acids located between positions 139 and 320 of ZYMV HC-Pro were associated with HEN1 interaction.,
Gesehen am 04.07.2022